Diagnosing COPD: advances in training and practice - a systematic review - Koblizek, Vladimir; Novotna, Barbora; Zbozinkova, Zuzana; Hejduk, Karel (Advances in medical education and practice, 2016)
Chronic obstructive pulmonary disease (COPD) is a chronic inflammatory lung syndrome, caused by long-term inhalation of noxious gases and particles, which leads to gradual airflow limitation. All health care professionals who care for COPD patients should have full access to high-quality spirometry testing, as postbronchodilator spirometry constitutes the principal method of COPD diagnosis. One out of four smokers 45 years or older presenting respiratory symptoms in primary care, have non-fully reversible airflow limitation compatible with COPD and are mostly without a known diagnosis. Approximately 50.0%-98.3% of patients are undiagnosed worldwide. The majority of undiagnosed COPD patients are isolated at home, are in nursing or senior-assisted living facilities, or are present in oncology and cardiology clinics as patients with lung cancers and coronary artery disease. At this time, the prevalence and mortality of COPD subjects is increasing, rapidly among women who are more susceptible to risk factors. Since effective management strategies are currently available for all phenotypes of COPD, correctly performed and well-interpreted postbronchodilator spirometry is still an essential component of all approaches used. Simple educational training can substantially improve physicians' knowledge relating to COPD diagnosis. Similarly, a physician inhaler education program can improve attitudes toward inhaler teaching and facilitate its implementation in routine clinical practices. Spirometry combined with inhaled technique education improves the ability of predominantly nonrespiratory physicians to correctly diagnose COPD, to adequately assess its severity, and to increase the percentage of correct COPD treatment used in a real-life setting.
Keywords: education; inhaled technique; spirometry; overdiagnosis; primary care; underdiagnosis